Representation of Gender in Contemporary Advertising: A Conceptual Extension of Goffman’s Framework - Misra, Deepika (2009)
Advertising is one of the most pervasive means of mass communication, and is widely acknowledged as a potent social artefact. In advertising, gender forms a fundamental basis for segmentation, and creation, of advertising design of verbal and visual rhetoric. In light of the strong relationship between gender and advertising, this study explores the representation of men and women in magazine advertisements. This study presents a conceptual extension of the gender display frameworks by (Belkaoui and Belkaoui, 1976), Goffman (1979), and extended by Kang (1997). A new category, ‘Eye Contact’ was also added to test as a relevant form of gender display. For this research, 167 advertisements from fashion and lifestyle magazines in the UK were analysed to assess the presence of gender stereotypes in the advertising characterisations and imagery. Previous research identified an overwhelming presence of gender-based stereotyping in advertisements in all forms of media. Women were often found to be associated with either domestic or sexualised contexts. Male images were characterised by professional settings, or in highly active, masculinised settings. Based on past research, this study explored the extent of gender stereotyping in contemporary advertisements based on location, setting, behavioural display, and magazine type. It further sought to investigate the applicability of Goffman’s gender stereotypes in contemporary advertising, and identify new ones. Content analysis revealed that gender stereotyping continues to exist in magazine advertisements. However, the degree and nature of stereotyping has changed. From Goffman’s criteria, ‘Relative Size’, and ‘Function Ranking’ were found to be no longer applicable to contemporary advertisements. Moreover, the study also found a high level of reverse stereotyping, with men observed to be displaying typically ‘feminine’ forms of behaviour, such as ‘Licensed Withdrawal’, ‘Feminine Touch’, and Body Display’. The distribution of images displaying ‘Body Display’ was observed to be equal between male and female images. The new category included in this study, ‘Eye Contact’ was found not to be a strong indicator for gender stereotyping. Additionally, research also revealed female-oriented magazines displayed a higher level of gender stereotyping than male-oriented magazines.